THE PERCEIVED CHALLENGES IN READING OF YOUNG LEARNERS - Hojiqulov, Shukrullo (Educational Research in Universal Sciences, 2023)
Reading is deemed to play a key role in the learning of English as a second language (ESL) among rural learners who have limited opportunities to hear or speak the language. However, they often come to ESL classrooms with the ability to read the text fluently, yet fully comprehend it. The past literature illuminate that these less skilled readers can be taught to employ appropriate reading strategies to construct the meaning from the text, and eventually aid their comprehension. Henceforth, this action research was conducted to explore how the twelve-week explicit strategy instruction via scaffolding approach helps improve eleven. The findings of this study revealed that all the some strategies play their own role in helping the participants to become active in creating meaning from the texts given, and thus enhancing their reading comprehension. Besides, the learners believe that the use of the strategies learnt improves their reading comprehension, promotes their higher order thinking skills, as well as motivates them to read. It is recommended that the explicit strategy instruction can be incorporated in teaching comprehension to primary ESL learners to aid their reading comprehension. The present paper is a report on a small classroom based research study. The teacher-researcher assigned two passages dealing with two different social issues and set in two different contexts, i.e., foreign and local, for comprehension to the students in the classroom. The classroom experience indicated that activating and building on the students’ background knowledge did help in facilitating their reading comprehension skills. The paper thus recommends it as an effective strategy to develop the young learners’ reading comprehension skills.